Circulating TNF receptor levels are associated with estimated glomerular filtration rate even in healthy individuals with normal kidney function - Tomohito Gohda; Maki Murakoshi; Terumi Shibata; Yusuke Suzuki; Hiroyuki Takemura; Koji Tsuchiya; Tomoki Okada; Mitsuru Wakita; Yuki Horiuchi; Yoko Tabe; Nozomu Kamei (Scientific Reports, 2024)
Abstract The association between serum tumor necrosis factor receptor (TNFRs: TNFR1, TNFR2) levels and estimated glomerular filtration rate (eGFR) observed in patients with diabetes has not been comprehensively tested in healthy subjects with normal kidney function. It also remains unclear whether TNFR levels differ by age and sex, and between healthy subjects and diabetics. We measured serum TNFR levels in 413 healthy subjects and 292 patients with type 2 diabetes. In healthy subjects, TNFR levels did not differ between men and women. Additionally, TNFR2, but not TNFR1, levels increased with age. In multivariate analysis, TNFR1 was associated only with cystatin C-based eGFR (eGFR-CysC), whereas TNFR2 was associated with systolic blood pressure in addition to eGFR-CysC. Both TNFRs were associated with lower eGFR (eGFR-Cys < 90 mL/min/1.73 m2) even after adjustment for relevant clinical factors. Upon combining healthy subjects and patients with diabetes, the presence of diabetes and elevated glycated hemoglobin level were significant factors in determining TNFR levels. TNFR levels were associated with eGFR-CysC, but were not affected by age and sex in healthy subjects with normal kidney function. TNFR levels in patients with diabetes appeared to be higher than in healthy subjects.